Comparative study of application of C4.5 algorithm and naïve bayes in selection partners of cooperation at PT. Citra Pesona Gemilang - Tri Hartati; Noer Hikmah; Heru Purwanto (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2022)
Currently, there are many companies whose line of business is education-oriented, which currently prioritizes technology as a source of information, and before a company enters into a cooperation contract with a vendor providing information technology equipment, many things need to be considered in determining the selection of partners where this consideration is very important to find out the prospect of profit that will be generated by the company from the cooperation. This research takes a case study at PT. Citra Pesona Gemilang whose company is engaged in providing various kinds of school needs. The cooperation partner of PT Citra Pesona Gemilang is a vendor of technology devices. In the research conducted, the authors use a decision-making method with the C4.5 algorithm and Naïve Bayes to determine the selection of the best cooperation partners. The selection is seen based on the quality and quantity of the product/service, the price of the product/service, the legality of the vendor, the superiority/reliability of the partner. The result of this study is to compare the level of accuracy produced by the two algorithms, namely the C4.5 algorithm and the Naïve Bayes algorithm in determining the selection of partners in the provision of information technology tools.